siRNA-mediated therapeutic approaches improve acute kidney injury and limit its worsening - Wang, Xijian; Huang, Xinzhong; Yang, Bin (Frontiers in Pharmacology, 2025)
Acute kidney injury (AKI) is a critical clinical condition, with high morbidity and mortality globally, and also often worsening or progresses to chronic kidney disease (CKD). Despite advances in supportive and replacement therapy, specific interventions remain limited, in term of targeting a molecule (s) involved in the mechanism underlying AKI and its chronic progression. Recent developments in the technology of RNA interference (RNAi), particularly small interfering RNA (siRNA), offer promising avenues for the specific modulation of genes involved in AKI. This review highlights the potential of siRNA-mediated gene therapy to mitigate AKI and prevent its worsening. Here, the properties and advantages of siRNA agents were addressed. More importantly, the existing research on siRNA chemical modifications and delivery systems enabled specific and precise treatments for AKI, while some extensively studied therapeutic approaches were addressed. Furthermore, the challenges and future prospects of siRNA-based drug development for AKI were discussed, with aims to nourish re-searchers and clinicians alike, and promote establishing efficient organ/cell targeted delivery systems and accelerate potential clinical applications.